1987
DOI: 10.1128/aem.53.3.489-494.1987
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Azotobacter vinelandii on Soil Nutrients

Abstract: Azotobacter vinelandii cells grew well in a medium made from soil and distilled water which contained little or no carbohydrate. They utilized p-hydroxybenzoic acid and other phenolic acids, soil nitrogen, and water-soluble mineral substances. Seventeen soils which supported excellent growth of A. vinelandii contained 11 to 18 different phenolic acids each, including p-hydroxybenzoic, m-hydroxybenzoic, vanillic, p-coumeric, syringic, cisand trans-ferrulic, and other unidentified aromatic acids. Three white, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
1
15
0
3
Order By: Relevance
“…Our results show that alpechin at concentrations ranging from 5 to 15% (v/v) positively affected mi- reported as similar to the natural environment [14]. Although the alpechin had some initial negative effects on growth and nitrogenase activity of Azotobacter, the negative effects disappeared after 24 h. Apparently A. chroococcum in dialyzed-soil media can tolerate high amounts of alpechin.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results show that alpechin at concentrations ranging from 5 to 15% (v/v) positively affected mi- reported as similar to the natural environment [14]. Although the alpechin had some initial negative effects on growth and nitrogenase activity of Azotobacter, the negative effects disappeared after 24 h. Apparently A. chroococcum in dialyzed-soil media can tolerate high amounts of alpechin.…”
Section: Discussionsupporting
confidence: 73%
“…Phenolic acids are energy-rich substances metabolized by some members of soil microorganisms, Azotobacter being prominent among them. In a previous work, Wu et al [14] and Moreno et al [16] reported that A . vinelandii can utilize phenolic acids as carbon and energy sources, suggesting that the growth of Azotobacter in soil and its ability to fix dinitrogen in natural environments depend on the amounts of available phenolic acids or polymers of these substances.…”
Section: Discussionmentioning
confidence: 94%
“…Certain simple phenolic compounds that have been shown to reduce A. vinelandii growth [42] have been identi¢ed in the phenolic fraction isolated from OMW extracts and it is therefore reasonable to anticipate the slow growth of A. vinelandii observed during the ¢rst bioremedation stages when the concentration of polyphenols in the medium is high. On the other hand, A. vinelandii may use phenolic compounds as carbon and energy sources in di¡erent soil extracts [20] and in pure growth media where particular ring cleavage enzymes for aromatic intermediates have been identi¢ed [19]. Phenolics such as phydroxybenzoic acid, which is a major simple phenolic compound in OMW, may be readily utilised [20,43] and support A. vinelandii growth [42].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, A. vinelandii may use phenolic compounds as carbon and energy sources in di¡erent soil extracts [20] and in pure growth media where particular ring cleavage enzymes for aromatic intermediates have been identi¢ed [19]. Phenolics such as phydroxybenzoic acid, which is a major simple phenolic compound in OMW, may be readily utilised [20,43] and support A. vinelandii growth [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation